Antibacterial Activity of As-Annealed TiO2 Nanotubes Doped with Ag Nanoparticles against Periodontal Pathogens - Sinem Yeniyol; Zhiming He; Behiye Yüksel; Robert Joseph Boylan; Mustafa Ürgen; Tayfun Özdemir; John Lawrence Ricci (Bioinorganic Chemistry and Applications)
It is important to develop functional transmucosal implant surfaces that reduce the number of initially adhering bacteria and they need to be modified to improve the anti-bacterial performance. Commercially pure Ti sheets were anodized in an electrolyte containing ethylene glycol, distilled water and ammonium fluoride at room temperature to produce TiO2 nanotubes. These structures were then annealed at 450°C to transform them to anatase. As-annealed TiO2 nanotubes were then treated in an electrolyte containing 80.7 g/L NiSO4·7H2O, 41 g/L MgSO4·7H2O, 45 g/L H3BO3, and 1.44 g/L Ag2SO4 at 20°C by the application of 9 V AC voltage for doping them with silver. As-annealed TiO2 nanotubes and as-annealed Ag doped TiO2 nanotubes were evaluated by SEM, FESEM, and XRD. Antibacterial activity was assessed by determining the adherence of A. actinomycetemcomitans, T. forsythia, and C. rectus to the surface of the nanotubes. Bacterial morphology was examined using an SEM. As-annealed Ag doped TiO2 nanotubes revealed intense peak of Ag. Bacterial death against the as-annealed Ag doped TiO2 nanotubes were detected against A. actinomycetemcomitans, T. forsythia, and C. rectus indicating antibacterial efficacy.